Potential Herbicidals and Growth Regulators Constituents in Rice Hulls of Oryza sativa - CHUNG, ILL-MIN; KIM, JONG-JIN; CHUN, SE-CHUL; AHMAD, ATEEQUE (Asian Journal of Chemistry, 2010)
Isolation and identifications of the compounds were done from the hulls of Oryza sativa. The main component of hulls momilactone A (1) and momilactone B (2) were reported as good herbicidals. Furthermore the isolation and identifications of two compounds were done from the hulls of Oryza sativa which gave the two compounds guanine (3) and nicotinamide (4) as reported an effective plant growth promoting factor. However, it has been suggested that rice hulls compounds, possess herbicidals as well as growth promoting substances. Such information might indicate the rice hulls contained two types of potential substances which constituents are useful as herbicidals and growth promoters.